Odpowiedzi

2010-03-23T16:23:55+01:00
A) x=-3+2y
3(-3+2y)+4y=1

x=-3+2y
-9+6y+4y=1

x=-3+2y
10y=10

x=-3+2
y=1
x=-1
y=1


b)x=-5y+4
3(-5y+4)-2y=-5

x=-5y+4
-15y+12-2y=-5

x=-5y+4
-17y=-17

x=-1
y=1
2010-03-23T16:25:50+01:00
A)
3x-2y+3=2x
3x +4y= 1

1x - 2y= -3 / x2
3x - 4y= 1

2x - 4y= -6
3x - 4y= 1

5x=-5 /5
x= -1

-2y= -3 - 1
-2y= -4 /-2
y=2

b)-2x+5y=-3x+4
3x-2y=-5

x + 5y= 4
3x - 2y= -5

x=4 - 5y
3(4-5y) - 2y= - 5
x=4 - 5y
12 - 15y - 2y= -5
x= 4- 5y
-17y=-17/-17
y=1
x=4 - 5x1
y=1
x=-1
2010-03-23T16:28:09+01:00
A) x=-3+2y
3(-3+2y)+4y=1
x=-3+2y
-9+6y+4y=1
x=-3+2y
10y=10
x=-3+2
y=1
x=-1
y=1
b)x=-5y+4
3(-5y+4)-2y=-5
x=-5y+4
-15y+12-2y=-5
x=-5y+4
-17y=-17
x=-1
y=1

wydaje mi się że dobrze